2008
DOI: 10.1159/000137644
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Vascular Endothelial Growth Factor, Receptor KDR and p53 Protein in Transitional Cell Carcinoma of the Bladder

Abstract: Aim: To evaluate the expression profile of vascular endothelial growth factor (VEGF), kinase-insert-domain-containing receptor (KDR) and p53 in patients from Northeastern China with transitional cell carcinoma (TCC) of bladder. Materials and Methods: One hundred and twelve patients with bladder transitional cell carcinoma were involved in this study. The expression of VEGF, KDR and p53 were evaluated by immunohistochemical staining on paraffin-embedded slides. The correlations between the biomarkers with clini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0
1

Year Published

2010
2010
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 35 publications
1
9
0
1
Order By: Relevance
“…In conclusion, a number of studies indicate that VEGF concentrations are prognostic for outcomes in bladder cancer [7,9–13,28]. Furthermore, clinical and pre‐clinical studies have indicated that adding anti‐VEGF therapies to TCC chemotherapy leads to improved treatment effectiveness, and clinical trials are under way to test these outcomes [37,38].…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…In conclusion, a number of studies indicate that VEGF concentrations are prognostic for outcomes in bladder cancer [7,9–13,28]. Furthermore, clinical and pre‐clinical studies have indicated that adding anti‐VEGF therapies to TCC chemotherapy leads to improved treatment effectiveness, and clinical trials are under way to test these outcomes [37,38].…”
Section: Discussionmentioning
confidence: 98%
“…Increased expression of VEGFR‐2 in TCC correlates with disease stage and increases with tumour invasion into the muscle [7,28]. VEGFR‐1 also is expressed in T‐24 cells [7] and in bladder cancer [26,28]. Therefore, we examined the effect of MMC on concentrations of VEGFR‐2 (KDR/flk‐1) and VEGFR‐1 (Flt‐1) Treatment with MMC did not change VEGFR‐1 mRNA in T‐24 cells.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Considering that tumor cells may express VEGF receptors [19,20,21], and that even non-receptor mediated SLT-VEGF toxicity might be cell-specific, we explored the sensitivity of Line IV Cl 1 melanoma cells to SLT-VEGF in vitro . We found that these cells are essentially negative for VEGFR-2 expression (Figure 1A) and their growth is inhibited by SLT-VEGF at a 100-fold higher IC 50 of 70 nM (Figure 1B).…”
Section: Resultsmentioning
confidence: 99%